Ni-Fe LATERIZATION TREND AND NICKEL Laterite prospect area determination ON LATERITE DEPOSITS IN LASOLO KEPULAUAN DISTRICT, NORTH KONAWE REGENCY, SOUTHEAST SULAWESI: POLA LATERISASI Ni-Fe DAN PENENTUAN AREA PROSPEK NIKEL LATERIT PADA ENDAPAN LATERIT DI KECAMATAN LASOLO KEPULAUAN, KABUPATEN KONAWE UTARA, SULAWESI TENGGARA - Rio Irhan Mais Cendra Jaya; Hasria; Haslan; Deniyatno; La Ode Asrafil; Laode Ihksan Juarsan; Al Firman; Indrawati; La Ode Sahidin; La Ode Andimbara; Alfirman (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2026)
This research was conducted in Lasolo Islands District, North Konawe Regency. This study aims to investigate the pattern of Ni Fe laterization and determine the prospect area of nickel laterite deposits. The method used is the analysis and interpolation of drilling data to determine Ni distribution, ore thickness, stripping ratio, and deposit prospect area. Drilling data are chemical data of several major elements and oxides obtained from XRF analysis, such as Ni, Fe, SiO2, MgO, and Al2O3, and ore thickness data. The laterization pattern show that the laterite nickel deposits at the research site belong to the saprolitic ore type where Ni tends to accumulate in the Saprolite Zone with Ni content higher than the Cut of Grade (COG) value. The results of interpolation and mapping obtained prospect areas are divided into three namely non-prospect areas (Ni <1.5%), areas with moderate enrichment prospects (Ni 1.5 - 1.8%), and areas with high enrichment prospects (Ni > 1.8%).